THE ROLE OF PARTNER INSTITUTIONS IN IMPROVING THE QUALITY STANDARDS OF PKBM BINA CIPTA UJUNGBERUNG THROUGH THE TRIPLE HELIX PARTNERSHIP PROGRAM - Holva Lovana Siregar; Jajat S. Ardiwinata; Asep Saepudin (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2022)
This research examines the role of partner institutions, namely government agencies, academic institutions and industrial institutions in improving the quality standards of PKBM units through the triple helix partnership program. This research uses a qualitative approach with descriptive methods. The data collection technique used is interviewing. The subjects of this study numbered 5 people consisting of 2 PKBM managers, 1 person from government institutions, 1 person from academic institutions and 1 more person from industrial institutions. The results showed that government institutions play a role in increasing human resources capacity, providing facilities, infrastructure and capital assistance and increasing and providing partnership network assistance. Academic institutions play a role in increasing HR capacity and improving partnership networks. While industrial institutions only play a role in providing capital assistance. The findings of this study show that PKBM Bina Cipta Ujungberung partner institutions have a role in improving the quality of PKBM units by increasing human resources capacity, providing facilities, infrastructure and capital assistance and improving and providing partnership network assistance.